Trust as an element for community participation in the Sustainable Development Goals (SDGs) localisation process in Malaysia / Mohd Idham Mohd Yusof ... [et al.] - Mohd Yusof, Mohd Idham; Yusof, Radduan; Ab Rahman, Farah Adilla; Sabri, Mohamad Fazli; Ariffin, Mariani; Tuan Ismail, Tuan Nooriani (2022)
In Malaysia, the process of localising the Sustainable Development Goals (SDGs) is still in its early stage, as just a handful of localities are committed to implementing the global agenda. In order to materialise the SDGs localisations concentrating on the community, the local government's top management must take aggressive measures and adopt a top-down and bottom-up strategy to encourage more community participation in the SDG-related activities. This article examines the implementation of the SDGs in three local governments, emphasising "community participation" and "trust" as the enabling factors. This qualitative study utilises in-depth interviews with five local government officials tasked with implementing the SDGs at their respective localities. The data were transcribed verbatim and analysed thematically. The study outcomes indicate that "trust" is the primary factor supporting community participation in SDG-related programmes. To ensure active community participation in SDG-related programmes, the "community trust" factor could be developed by focusing on: a) internal and external stakeholder partnerships, b) community engagement, c) reward and recognition, and d) designing interactive programmes. The tactics mentioned above were advised to be bolstered by multi-stakeholder engagement and community inclusion principles. Active community participation in local government activities has been shown to sustain SDG-related programmes and empower the community effectively. Owing to the limited number of selected local governments, the findings of this study cannot be generalised. This research solely selects local governments from Malaysia's north and south region. Therefore, future research should expand the number of local governments evaluated based on Malaysia's region and incorporate a quantitative approach with a public survey. To enhance community participation in the SDG's localisation process, other components such as local leadership, multi-stakeholders roles, and the use of technology might be further explored.